THE ENVIRONMENTAL, SOCIAL AND ECONOMIC EFFECTS OF RECENT TECHNOLOGICAL CHANGES IN SUGARCANE ON THE STATE OF SAO PAULO, BRAZIL - Baccarin, Jose Giacomo [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2019)
The Agro-Environmental Protocol of the Sugar-Energy Sector was in force in the state of Sao Paulo between 2007 and 2017. This protocol consisted of an agreement between sugar-ethanol producers and the Government of the State of Sao Paulo, proposing to eliminate the pre-harvest burning of sugarcane as a method for facilitating its harvest while simultaneously replacing manual by mechanical harvesting. This work details the reasons leading to sugarcane mechanization, its consequences on land concentration, and competition between agribusinesses and sugarcane suppliers. The effects on the formal labor market are estimated and discussed since a sharp drop in the number of sugarcane cutters and the increasing number of workers in agricultural mechanization, transportation, equipment maintenance and administrative services led to a negative balance. It is understood the public action on the Protocol was partial since it prioritized the environmental issue while showing little concern regarding the employment and the resulting economic concentration.
Keywords: Agricultural Worker; Agricultural Mechanization; Economic Concentration; Land Structure; Sustainability